Extending the limits of force endurance: Stimulation of the motor or the frontal cortex?. (December 2017) - Radel, Rémi; Tempest, Gavin; Denis, Gauthier; Besson, Pierre; Zory, Raphael
Abstract: Previous findings indicate that facilitation of primary motor cortex (PMC) activity using trans-cranial direct current stimulation (tDCS) could improve resistance to physical fatigue. However, studies have failed to consistently replicate these results. Using non-focal-tDCS during a fatiguing task, recent work showed no enhancement of corticospinal excitability of the PMC despite a longer endurance time and suggested that contamination in other brain regions involved in motor command may have occurred. In accordance with recent evidence supporting the role of the prefrontal cortex (PFC) in exercise maintenance, this double-blind sham-controlled crossover study ( N  = 22) compared the effect of high definition (HD)-tDCS of the PMC or the PFC on endurance time of a sustained contraction task of the elbow flexor. Brain activity was monitored using near infrared spectroscopy (NIRS) to measure the neurovascular response elicited by HD-tDCS. Electromyography (EMG) and force obtained during maximal voluntary and evoked contractions were assessed before and after the contraction task to explore the effect of brain stimulation on peripheral and central fatigue. While the stimulation affected the brain response in the PFC during the contraction task, no effects of the stimulation were observed on endurance time or fatigue indices. These results are discussed in relation to the neurocognitive models of physical effort.